Modeling chloramine decay in full‐scale drinking water supply systems. (3rd February 2019) - Ricca, Henry; Aravinthan, Vasanthadevi; Mahinthakumar, Gnanamanikam
Abstract: Chloramines are commonly used as secondary disinfectants in drinking water treatment, providing a residual for disinfection as drinking water moves to consumers. Chloramines are inherently unstable, undergoing autodecomposition reactions even in the absence of reactive substances. In the presence of natural organic matter (NOM), chloramine loss accelerates due to additional reaction pathways. In this study, batch reaction models for chloramine loss due to autodecomposition and the presence of NOM were developed. A case study was carried out for the Town of Cary, North Carolina. A hydraulic model of Cary's distribution system was developed and calibrated using the EPANET toolkit with operational and water demand data supplied by Cary. Then, water age from the hydraulic model was used together with the batch model of chloramine decay to successfully predict chloramine concentrations spatially and temporally throughout the network. The capabilities of the EPANET‐MSX toolkit to model chloramine loss in a distribution network are explored. Practitioner points: A batch reaction model of chloramine decay over time due to autodecomposition reactions and additional reactions with NOM was developed and validated. A hydraulic model of the Town of Cary's water distribution network was developed and calibrated using operational and water demand data. Water age reported by the calibrated hydraulic model was used in conjunction with the batch reaction model of chloramine decay to successfully predict chloramine concentrations spatially and temporally throughout the network.